The politics of party funding state funding to political parties and party competition in western Europe - Koss, Michael (Oxford : Oxford University Press, 2011)
'The Politics of Party Funding' analyses an increasingly popular institutional choice - the introduction of state funding to political parties - and represents a first step towards a theory which explains differences and similarities in party funding regimes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Campaign funds -- Europe, Western